2017
DOI: 10.1002/esp.4109
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene outburst floods from Issyk Kul, Kyrgyzstan?

Abstract: Elevated shorelines and lake sediments surrounding Issyk Kul, the world's second largest mountain lake, record fluctuating lake levels during Quaternary times. Together with bathymetric and geochemical data, these markers document alternating phases of lake closure and external drainage. The uppermost level of lake sediments requires a former damming of the lake's western outlet through the Boam gorge. We test previous hypothesised ice or landslide dam failures by exploring possible links between late Quaterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…All three approaches take advantage of the incipient motion principle and compute velocities for turbulent, Newtonian fluid flow when a sediment grain of given intermediate grain diameter initiates motion on the stream's bed. The Gauckler-Manning formula (Gauckler, 1867;Manning, 1891) was then used to estimate peak discharge from the peak flow velocity determined above and the valley cross-sectional geometry using the numerical optimization scheme of Rosenwinkel et al (2017). Peak discharges and maximum flood heights were calculated from flow velocities using the average of two valley cross-sections and bed slope for each boulder considered (S2).…”
Section: Paleo-hydrologic Discharge Estimationmentioning
confidence: 99%
“…All three approaches take advantage of the incipient motion principle and compute velocities for turbulent, Newtonian fluid flow when a sediment grain of given intermediate grain diameter initiates motion on the stream's bed. The Gauckler-Manning formula (Gauckler, 1867;Manning, 1891) was then used to estimate peak discharge from the peak flow velocity determined above and the valley cross-sectional geometry using the numerical optimization scheme of Rosenwinkel et al (2017). Peak discharges and maximum flood heights were calculated from flow velocities using the average of two valley cross-sections and bed slope for each boulder considered (S2).…”
Section: Paleo-hydrologic Discharge Estimationmentioning
confidence: 99%
“…It is worth noting that under the influence of the AMO, changes in the lake water level do not exhibit cyclical fluctuations (Figure 7), which suggests that, apart from the effects of climate, lake water levels have also been affected by the Chu River separation, regional anthropogenic disturbance, and lake basin subsidence (Abuduwaili et al, 2019; Romanovsky, 2002; Rosenwinkel et al, 2017; Salamat et al, 2015). Before 1860 AD, the C/N and MS contents were relatively high (Figure 3), the replenishment and drainage effects of the Chu River and other exogenous rivers caused the TOC contents to be influenced only slightly, and the lake water level was high and relatively stable.…”
Section: Discussionmentioning
confidence: 99%
“…After 1860 AD, the values of C/N and MS obviously decreased (Figure 3), suggesting that exogenous rivers may have migrated, that the Chu River may have separated from Lake Issyk-Kul and that the TOC contents fluctuated notably as the lake level declined significantly (Figure 6; Podrezov et al, 2020;Romanovsky, 2002;Rosenwinkel et al, 2017). Some studies have indicated that Lake Issyk-Kul has become an endorheic lake due to the separation of the Chu River over the past 150 years (Giralt et al, 2004).…”
Section: Chu River Separation and Anthropogenic Disturbancementioning
confidence: 99%
See 1 more Smart Citation
“…1.3 significant GLOF events per year (Veh et al, 2019). A modern inventory of LLOFs has not been compiled as systematically, but recent reviews also suggest widespread occurrences along the Himalayan range (Ruiz-Villanueva et al, 2017). Since most of the existing information about LOFs in the Himalayas is derived from observational or historical records, limited insight is available with respect to the maximum magnitudes that can be expected for these events or the evolution of their occurrence frequency through time, for example in response to climatic change.…”
mentioning
confidence: 99%